2007
DOI: 10.1128/mcb.01975-06
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahymena POT1a Regulates Telomere Length and Prevents Activation of a Cell CycleCheckpoint

Abstract: The POT1/TEBP telomere proteins are a group of single-stranded DNA (ssDNA)-binding proteins that have long been assumed to protect the G overhang on the telomeric 3 strand. We have found that the Tetrahymena thermophila genome contains two POT1 gene homologs, POT1a and POT1b. The POT1a gene is essential, but POT1b is not. We have generated a conditional POT1a cell line and shown that POT1a depletion results in a monster cell phenotype and growth arrest. However, G-overhang structure is essentially unchanged, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 53 publications
4
55
1
Order By: Relevance
“…Human POT1 (hPOT1) and hPOT1V2 (a splice variant of hPOT1 composed of its DNA-binding domain, used extensively to characterize POT1 structurally and biochemically) bind telomeric DNA with high affinity (K D ∼ 10 nM) and base specificity (10). POT1 is conserved among all mammals and has functional homologs in other species such as Oxytricha nova (12), Tetrahymena thermophila (13), and Schizosaccharomyces pombe (6,14). A sequence-related protein in the plant Arabidopsis thaliana associates with the telomerase ribonucleoprotein rather than the telomeric DNA (15)(16)(17).…”
mentioning
confidence: 99%
“…Human POT1 (hPOT1) and hPOT1V2 (a splice variant of hPOT1 composed of its DNA-binding domain, used extensively to characterize POT1 structurally and biochemically) bind telomeric DNA with high affinity (K D ∼ 10 nM) and base specificity (10). POT1 is conserved among all mammals and has functional homologs in other species such as Oxytricha nova (12), Tetrahymena thermophila (13), and Schizosaccharomyces pombe (6,14). A sequence-related protein in the plant Arabidopsis thaliana associates with the telomerase ribonucleoprotein rather than the telomeric DNA (15)(16)(17).…”
mentioning
confidence: 99%
“…This length of overhang is insufficient for binding both Pot1a and Teb1 (34). Because Pot1a depletion triggers runaway telomere elongation even in nondividing cells (24), telomerase exclusion from chromosome termini may depend on a low off-rate of Pot1a from bound DNA achieved in part by Pot1a interactions with other telomere proteins (25,47). Alternately, Teb1 binding to telomeres could be competed by RPA, with subsequent RPA replacement by Pot1a complexes.…”
Section: Discussionmentioning
confidence: 99%
“…This potentially constitutive assembly of holoenzyme is different from the paradigm set by yeast telomerase holoenzyme subunit regulation by the cell cycle (11,12,21,30). Nonetheless, constitutive Tetrahymena telomerase holoenzyme assembly would be consistent with the dramatic elongation of telomeres in nondividing cells depleted of the Pot1a-Tpt1-Pat1-Pat2 complex (24).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Carolyn Price (University of Cincinnati) showed that another of these proteins, POT-1, negatively regulates telomere length, likely through competition with telomerase for the chromosome end (Churikov et al 2006). She also concluded that, during the cell cycle, POT-1 mediates an essential checkpoint in Tetrahymena (Jacob et al 2007). Finally, Julia Cooper (Cancer Research UK) discussed how telomere-associated proteins are necessary for proper chromosome segregation during meiosis in S. pombe.…”
Section: Telomerase and Telomeresmentioning
confidence: 99%